Bibliometric Study of Scientific Production on ICT in Perú (2010-2017) - Asmat Vega, Nicanor Segismundo (2019)
The objective of this research is to evaluate Peruvian scientific production in Information and Communication Technologies (ICTs). It is a cross-sectional descriptive study through the bibliometric analysis of articles published in journals indexed in SciELO Peru between 2010 and 2017. Authorship, type of article, main themes, and institutional productivity were analyzed. It was found that between 2010 and 2017, 19 articles on ICT were published, 26.4% of them are publications in the Peruvian Journal of Experimental Medicine and Public Health, and 30.8% of authors indicate that their main affiliation is with the National University of San Marcos. The main theme in the set of publications was virtual teaching (26%). We can conclude that technological development is contributing to the scientific publication of the country; however, it is necessary to continue strengthening these studies in other databases.